Patterns of Antimicrobial Use Among Nursing Home Residents With Advanced Dementia - D’Agata, Erika (2008)
BACKGROUND: Nursing home residents with advanced dementia are at high risk of infections and antimicrobial exposure near the end of life. Detailed studies quantifying antimicrobial prescribing practices among these residents have not been performed. METHODS: A cohort of 214 residents with advanced dementia from 21 Boston-area nursing homes were followed up prospectively for 18 months or until death. We analyzed antimicrobial use, including type, indication, and quantity, by days of therapy per 1000 resident-days. RESULTS: During an average of 322 days of follow-up, 142 residents (66.4%) with advanced dementia received at least 1 course of antimicrobial therapy (mean [SD] number of courses per resident, 4.0 [3.7]). The mean (SD) number of days of therapy per 1000 resident-days for the entire cohort was 53.0 (4.3). Quinolones and third-generation cephalosporins were the most commonly prescribed antimicrobials, accounting for 38.3% and 15.2%, respectively, of 540 prescribed antimicrobial therapy courses. A respiratory tract infection was the most common indication (46.7% of all antimicrobial therapy courses). Among 99 decedents, 42 (42.4%) received antimicrobials during the 2 weeks before death, of which 30 of 72 courses (41.7%) were administered via the parenteral route. The number of decedents receiving antimicrobials (P< .001), the number of antimicrobials prescribed (P=.01), and the days of therapy per 1000 resident-days (P< .001) increased significantly as subjects approached death. CONCLUSIONS: Persons with advanced dementia are frequently exposed to antimicrobials, especially during the 2 weeks before death. The implications of this practice from the perspective of the individual treatment burden near the end of life and its contribution to the emergence of antimicrobial resistance in the nursing home setting need further evaluation.